WASTE WATER TREATMENT IN SPACE CONDITIONS - Dolyna, L. F.; Zhdan, Y. O.; Dolyna, D. A. (Science and Transport Progress, 2020)
Purpose. The main purpose of the article is to develop a technology for wastewater treatment in space. Methodology. The studies were performed based on the analysis of Ukrainian and foreign scientific sources and reporting data on the specifics of water use at space stations and the treatment methods of the used waters (wastewaters). In addition to international experience, our own research was used to develop a technology for wastewater treatment in space. Findings. A comprehensive review of the issues related to wastewater treatment in space, allows us to conclude that it is necessary to regenerate water at International space stations (ISS). Indeed, to ensure the life support of the astronauts, a colossal amount of water is required, and its delivery to the ISS from the Earth is expensive. Originality. The authors of the article analyzed the operation of existing wastewater treatment facilities in space and made recommendations for their use at the ISS. The developed technology for the treatment of wastewater and drinking water in zero-gravity (space) is based on the use of various reactors. They can be made of various materials (metal, plastic, etc.); they do not contain non-standard equipment that requires factory manufacturing. Compactness, complete tightness and small dimensions of bio- and physicochemical reactors allow them to be installed within the ISS. The cleaning process is easy to manage and can be fully automated. Practical value. Water problems are central to the whole world, including in space. The ISS should have a system for the wastewater treatment and their closed use, since the supply of new water to stations significantly increases the cost of space exploration. Quality water is the health and well-being of people in space. Since there is no gravity in space, centrifugal forces (centrifuges) must be used to separate suspended particles from water.